Emerging Applications of Augmented Reality System for Future Industry - Angelin Rosy, M; Umarani, L; V, M (International Journal of Computer Sciences and Engineering, 2025)
Augmented Reality (AR) makes the real-life environment about us into a digital interface by putting virtual objects in real time. It Augmented Reality Apps are software applications which merge the digital visual (audio and other types also) content into the user’s real-world environment. This project focus on the use of desktop display interfaces for applications of augmented reality (AR), there are including the games, education, business, medical, etc. This type of interface, the user is able to look at a screen and see the computer-generated graphics displayed above markers. In AR process overviews of desktop display interface alleviate most of the problems associated with head mounted displays (HMDs). AR applications also require removing real objects from the perceived environment in addition to adding virtual real objects environment.